Library networks and library systems kernel port heads (continued) - Lau Williams, Violeta (1980)
The school libraries play a very important paper in the communities, on these it depends the possible and future influences that are met related by the economic, social, political, cultural and psychological aspects projected to the communal well-being. As the technological and scientific advance goes there being increased equally the need to possess information and documentation grows. In Nicaragua, by means of the Department of Education one tries to implant a national cooperative plan for all the libraries that will form a part of the System of School Libraries.